2015
DOI: 10.3906/biy-1408-18
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and cytotoxic properties of boron-containing dental composite

Abstract: Secondary dental caries are one of the major reasons for restoration replacements. Incorporating antimicrobial properties into dental materials would limit the initiation and progression of dental caries. In the current study, dental composites having 1%, 5%, and 10% (w/w) sodium pentaborate pentahydrate were prepared and analyzed for their mechanical properties, degree of monomer conversion (DC) rate, antibacterial effects against Streptococcus mutans, and biocompatibility with human dental pulp stem cells (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Although it is well-known that the ions in an S-PRG eluate are involved in various mechanisms, the antibiofilm mechanism has not yet been determined. According to previous studies, BO 3 3− is known to exhibit antibacterial activity and quorum sensing inhibition 20,21 . Dembitsky et al 22 demonstrated the inhibitory effect www.nature.com/scientificreports/ of BO 3 3on quorum sensing in fungi; this indicates the role of S-PRG in inhibiting quorum sensing, which is a key component in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well-known that the ions in an S-PRG eluate are involved in various mechanisms, the antibiofilm mechanism has not yet been determined. According to previous studies, BO 3 3− is known to exhibit antibacterial activity and quorum sensing inhibition 20,21 . Dembitsky et al 22 demonstrated the inhibitory effect www.nature.com/scientificreports/ of BO 3 3on quorum sensing in fungi; this indicates the role of S-PRG in inhibiting quorum sensing, which is a key component in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, positive effect of B on osteogenic differentiation of MC3T3‐E1 pre‐osteoblastic cell was shown (Gümüşderelioğlu et al, ; Hakki, Bozkurt, & Hakki, ). Additionally, it has been reported that B addition enhanced the osteogenic and odontogenic differentiation potential of dental stem cells (Demirci et al, ; Taşlı, Doğan, Demirci, & Şahin, ). In our previous study, positive effect of B‐modified bioactive glass nanoparticles (BG‐NPs) on odontogenic differentiation of hDPSCs was observed (Moonesi Rad et al, ; Moonesi Rad Atila et al, ; Moonesi Rad et al, )…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, positive effect of MTA mixed with 5% CaCl 2 or 2.5% Na 2 HPO 4 was detected for mineralization of hDPSCs. 87 Demirci et al 15 prepared dental composites including 1%, 5%, and 10% (w/w) sodium pentaborate pentahdrate. Ten days after incubation of hDPSCs seeded composites in odontogenic medium, elevated levels of calcium deposition in all boron-containing composites were observed.…”
Section: Evaluation Of Differentiation Of Hdpscs Seeded On 3d Scaffoldsmentioning
confidence: 99%
“…9 Different studies confirmed positive effects of B on proliferation of human osteoblasts and mesenchymal stem cells, 10,11 osteogenic differentiation of pre-osteoblastic cells, 12,13 and osteogenic and odontogenic differentiation of dental stem cells. 14,15 In our previous study, modification of BG with B promoted proliferation and odontoblastic differentiation of human dental pulp stem cells (hDPSCs). 16 Proteins, polysaccharides, and synthetic polymers constitute organic part of the scaffolds.…”
Section: Introductionmentioning
confidence: 98%